A importância da sala de leitura como “espaço” de letramento de alunos dos anos iniciais - SANTOS, Maria do Socorro dos Santos e (2019)
This work deals with the importance of the reading room as a space of literacy in the initial years, aiming to understand the processes of acquisition of reading and construction of knowledge, from the reading practices and the development of the reader, through the use of literary genres . The same was developed by bibliographic and field research, through the daily experience with the students as a reading room teacher, in the application of significant activities in this learning process, allowing the analysis and reflection on the real purpose of the reading room in the formation of individual and seeking to re-signify this space giving meaning to the true act of teaching.